Polyesterification of Shellac as An Alternative Coating Material - Lestari Hetalesi Saputri; Rochmadi Rochmadi; Budhijanto Budhijanto (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Polyester resin is a type of polyester that is widely used in daily life, such as for paints, coating, composite matrix and so on. However, the widely used is a synthetic resin polyester. They have durable properties and extremely difficult to be degraded. While, the natural polyesters have weakness in their mechanical properties. This research aimed to modify shellac, one of natural polyesters, with phtalic anhydride in order to improve properties of coating material. The Addition of phtalic anhydride is expected to increase the hardness so that is not easily broken. FTIR analysis indicated the presence of esters and carboxylic acid groups, whereas the hardness test showed that polyester with a ratio of COOH/OH 0.7 had a higher hardness. The hardness level for polyester with the ratio of 0.7 was also reinforced by the degree of crystallinity shown by XRD analysis. It could be expected that modification shellac might be one of an alternative way to produce a material coating which is more environmentally friendly